The impact of chewing betel nuts on human dentition in Indonesia: A literature review - Alaydrus, Sayf Muhammad; Artaria, Myrtati Dyah; Chen, Yao-Fong (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Human behavior can significantly alter dental conditions. One such behavior is the habit of chewing betel nuts. Known as nginang, this tradition holds social significance in many cultures across Indonesia. Societal beliefs include the idea that chewing betel nuts offers a sensation similar to smoking cigarettes, provides a pastime, reduces bad breath, and even enhances dental health. However, evidence shows that it can cause severe damage to teeth. Purpose: This research aims to analyze the literature regarding the impact of chewing betel nuts on dental conditions and to recommend actions to address the problems caused by it. Reviews: While this habit can have positive aspects, it may also cause tooth damage when practiced with a certain frequency and intensity and using specific compositions. Issues such as calculus, periodontitis, attrition, and antemortem tooth loss may occur due to this habit. However, inconsistencies have been found concerning this habit's relation to caries. Conclusion: A pathological chain reaction triggered by betel nut chewing confirms its detrimental effect on dental health. Further investigations are required to explain the inconsistencies found in this review. The researchers recommend promoting tooth brushing to enable society to maintain its tradition without risking further teeth damage.